A thermal desorption ion mobility spectrometer for the measurement of anticoagulant rodenticide diphacinone in beverages via in situ acid-assisted conversion. Issue 3 (19th December 2014) - Peng, Liying; Wang, Xin; Chen, Wendong; Zhou, Qinghua; Wang, Weiguo; Li, Haiyang
Abstract : TD-IMS was constructed for fast detection of rodenticide diphacinone via in situ acid-assisted conversion and applied for its on-site determination in beverages. Abstract : Anticoagulant rodenticide diphacinone (DPN) with the common form of sodium diphacinone (SDPN), playing an important role in controlling field rodents and mice in homes, is harmful to both human beings and domestic animals while taken mistakenly or poisoned intentionally. In this work, we propose a simple and rapid method based on thermal desorption ion mobility spectrometry (TD-IMS) for detecting DPN and SDPN. SDPN, with ultra-low vapour pressure, was essentially measured in the form of DPN after its in situ conversion with the assistance of an acid. Under the optimal conditions, the limits of detection ( S / N = 3) for SDPN and DPN were less than 0.15 ng μL −1 while their recoveries were 96% and 97%, respectively, and the relative standard deviation for five measurements was less than 6.15%. Finally, the current method was used to detect DPN and SDPN in beverages including green tea, cola, and coffee, demonstrating its capacity in the application for actual samples.